2014
DOI: 10.3389/fonc.2014.00245
|View full text |Cite
|
Sign up to set email alerts
|

Involvement of Platelet–Tumor Cell Interaction in Immune Evasion. Potential Role of Podocalyxin-Like Protein 1

Abstract: Besides their essential role in hemostasis and thrombosis, platelets are involved in the onset of cancer metastasis by interacting with tumor cells. Platelets release secretory factors that promote tumor growth, angiogenesis, and metastasis. Furthermore, the formation of platelet–tumor cell aggregates in the bloodstream provides cancer cells with an immune escape mechanism by protecting circulating malignant cells from immune-mediated lysis by natural killer (NK) cells. Platelet–tumor cell interaction is accom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
46
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 56 publications
(47 citation statements)
references
References 91 publications
1
46
0
Order By: Relevance
“…L-selectin on leukocytes acts synergistically with P-selectin, facilitating platelet-tumor interaction (Borsig et al, 2002). Podocalyxin-like protein 1 (PCLP1) binds E- and L-selectin in pancreatic cancer (Dallas et al, 2012), and is overexpressed in many cancers and on activated platelets (Amo et al, 2014). Once activated, platelets can then bind to tumor cells via P-selectin (Chen and Geng, 2006; Coupland et al, 2012; Qi et al, 2015) and glycoproteins (Lonsdorf et al, 2012; Goubran et al, 2013) and directly induce tumor growth and metastasis by releasing pro-tumor angiogenic and growth factors.…”
Section: Platelets and Cancer Progressionmentioning
confidence: 99%
See 1 more Smart Citation
“…L-selectin on leukocytes acts synergistically with P-selectin, facilitating platelet-tumor interaction (Borsig et al, 2002). Podocalyxin-like protein 1 (PCLP1) binds E- and L-selectin in pancreatic cancer (Dallas et al, 2012), and is overexpressed in many cancers and on activated platelets (Amo et al, 2014). Once activated, platelets can then bind to tumor cells via P-selectin (Chen and Geng, 2006; Coupland et al, 2012; Qi et al, 2015) and glycoproteins (Lonsdorf et al, 2012; Goubran et al, 2013) and directly induce tumor growth and metastasis by releasing pro-tumor angiogenic and growth factors.…”
Section: Platelets and Cancer Progressionmentioning
confidence: 99%
“…Platelets and platelet-derived microparticles adhere to tumor cells through interactions with integrins and selectins (Kitagawa et al, 1989; Felding-Habermann et al, 1996; Gay and Felding-Habermann, 2011). Additionally, fibronectin and other adhesive molecules may act as a bridge between platelets and tumor cells, as mediated by PCLP1 (Amo et al, 2014). Tumor cells are enshrouded in platelet-fibrin mesh, shielding them from NK cell contact and immune surveillance in circulation (Borsig et al, 2001).…”
Section: Platelets and Cancer Progressionmentioning
confidence: 99%
“…There is growing evidence suggesting the co-operative behaviour exhibited by cells within CTMs can promote mutual survival and increased tumorigenic potential (16,33,(141)(142)(143)(144). It has also been suggested that interactions between blood cell and platelets can benefit both CTMs and single CTCs by protecting them from the host immune system (134,(145)(146)(147). Cellular cooperation has been elegantly demonstrated using a model derived from hamster oral keratinocytes of both mesenchymal and epithelial cells (148).…”
Section: Circulating Tumour Microemboli (Ctm)mentioning
confidence: 99%
“…In fact, in such clusters, migrating malignant cells are surrounded by a platelet shield that may provide mechanical protection from physical damages. Moreover, activated platelets may facilitate tumor cell survival utilizing TGF-b or PDGF-related signaling pathways resulting in the inhibition of the effector functions of natural killer cells [63,64] or may mask tumor cells, and thus prevent their recognition by natural killer cells [65][66][67]. Accordingly, inhibition of platelet activity results in the enhanced cytotoxic activity of natural killer cells [68].…”
Section: Activation Loop Between the Endothelium Platelets And Tumormentioning
confidence: 99%